Perbandingan rencana strategi pada BSI, Bank Muamalat, dan BTN Syariah dengan analisis SWOT - Hestiyanti, Siti Fatimah; Ariba, Nadia; Jasmine, Ken Catri Amira (Maliki Interdisciplinary Journal, 2023)
Sharia Bank is a bank that carries out its business activities based on sharia principles. Sharia principles are legal principles regulated in the Islamic religion. The existence of sharia banks in Indonesia has grown since they were first introduced in Indonesia in 1992. Bank Muamalat was the starting point for the sharia banking system in Indonesia, from there the establishment of other sharia banks such as Bank Mandiri Syariah, BRI Syariah, BNI Syariah which have merged into BSI (Bank Syariah Indonesia) and BTN Syariah. Each Sharia Bank has its own vision, mission and goals. To achieve the vision and mission that have been set, a strategic plan is needed. As the development of Sharia Banking creates competition between these banks. This research uses SWOT analysis to find out the comparison of strategic plans between Bank Muamalat, BSI and BTN Syariah. From this comparison, you can find out which strategic plan is superior and know the strengths and weaknesses of each.